Latin-into-Hebrew : texts and studies. - Fontaine, Resianne, 1953-; Freudenthal, Gad; Freudenthal, Gad. (Leiden ; Boston : Brill, 2013)
This two-volume work, 'Latin-into-Hebrew: Texts and Studies' sheds new light on an under-investigated phenomenon of European medieval intellectual history: the transmission of knowledge and texts from Latin into Hebrew between the twelfth and the fifteenth century. Because medieval Jewish philosophy and science in Christian Europe drew mostly on Hebrew translations from Arabic, the significance of the input from the Christian majority culture has been neglected. 'Latin-into-Hebrew: Texts and Studies' redresses the balance. It highlights the various phases of Latin-into-Hebrew translations and considers their disparity in time, place, and motivations. Special emphasis is put on the singular role of the translations of Latin medical and philosophical literature. 'Volume One: Studies', offers 18 studies and 'Volume Two: Texts in Contexts', includes editions and analyses of hitherto unpublished texts of medieval Latin-into-Hebrew translations.
Volume 1. Studies -- volume 2. Texts in Contexts / edited by Alexander Fidora, Harvey J. Hames, Yossef Schwartz.
Includes bibliographical references and indexes.
LC has volume 1 only.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Literature, Medieval -- Translations into Hebrew; Classical literature -- History and criticism; Judaism -- History -- Medieval and early modern period, 425-1789.; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Translating and interpreting -- Social aspects; LITERARY CRITICISM / African; Electronic books